ANALISIS KINERJA PEGAWAI KANTOR PERTANAHAN DI MAKASSAR - Dewi Pratiwi Indriasatri (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aimed to test the effects of each independent variable: work capability, and motivation, on staff performance. Data were obtained from an observation method according to field conditions as well as from questionnair dissemination to the study respondents. Analysis instrument used was Kendall’s Tau Correlation using an SPSS version 12.0. The study resulted in a positive and significant relationship between the independent variables (work capability, and motivation) on staff work performance at Agrarian Office in Makassar on the scales of 0.217 (work capability), and 0.491 (motivation), In addition, collective significance rate of the relationship between the three variables and the staff performance was 73.16%.